2012
DOI: 10.1016/j.bbamcr.2012.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence correlation spectroscopy, combined with bimolecular fluorescence complementation, reveals the effects of β-arrestin complexes and endocytic targeting on the membrane mobility of neuropeptide Y receptors

Abstract: Fluorescence correlation spectroscopy (FCS) and photon counting histogram (PCH) analysis are powerful ways to study mobility and stoichiometry of G protein coupled receptor complexes, within microdomains of single living cells. However, relating these properties to molecular mechanisms can be challenging. We investigated the influence of β-arrestin adaptors and endocytosis mechanisms on plasma membrane diffusion and particle brightness of GFP-tagged neuropeptide Y (NPY) receptors. A novel GFP-based bimolecular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
58
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(61 citation statements)
references
References 64 publications
3
58
0
Order By: Relevance
“…Graphs show pooled competition data (n = 5), from which the pIC 50 values in Table 2 The functional Y 4 R agonism produced by the peptides was analysed using a β-arrestin2 recruitment assay to detect Y 4 R activation (Figure 4), as previously described. 39,40 One advantage of this assay is its limited receptor reserve, which improves correspondence between agonist potency (as EC 50 , the concentration of agonist that produces 50% of its maximal response) and underlying functional receptor affinities, and also the likelihood that differences in agonist intrinsic efficacy are revealed through changes in relative maximum response (R max ). 41 Thus the reference agonist human PP stimulated β-arrestin2 association with an EC 50 value (2.6 nM) very similar to its derived pIC 50 in the whole cell Y 4 R binding experiments.…”
Section: = Not Determinedmentioning
confidence: 99%
“…Graphs show pooled competition data (n = 5), from which the pIC 50 values in Table 2 The functional Y 4 R agonism produced by the peptides was analysed using a β-arrestin2 recruitment assay to detect Y 4 R activation (Figure 4), as previously described. 39,40 One advantage of this assay is its limited receptor reserve, which improves correspondence between agonist potency (as EC 50 , the concentration of agonist that produces 50% of its maximal response) and underlying functional receptor affinities, and also the likelihood that differences in agonist intrinsic efficacy are revealed through changes in relative maximum response (R max ). 41 Thus the reference agonist human PP stimulated β-arrestin2 association with an EC 50 value (2.6 nM) very similar to its derived pIC 50 in the whole cell Y 4 R binding experiments.…”
Section: = Not Determinedmentioning
confidence: 99%
“…The effect of DAMGO was not sensitive to PTX but was abolished by high sucrose, suggesting that it was related to the endocytosis process (46). A more recent study on neuropeptide Y (NPY1 and NPY2) receptors, combining FCS associated with photon counting and BiFC, showed that the NPY-induced receptor slowing down and clustering (measured as an increase in particle brightness) was due to the recruitment of ␤-arrestin, the first step before internalization (67). On the other hand, the binding of antagonists has been generally described to produce no modification of the lateral mobility of receptors (37,39,46,67,68), as we observed here with naloxone.…”
Section: Discussionmentioning
confidence: 99%
“…This contrasts with what is generally observed when receptors are activated by their own agonists. For a majority of GPCR, the binding of agonists decreases the mobility of receptors by reducing their diffusion coefficient and/or by restricting their movement in smaller membrane domains (39,46,67). This probably reflects the early events preceding endocytosis processes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Betaarrestins are multifunctional proteins that contribute to desensitization of G-protein-coupled receptors (GPCRs) by blocking the receptor × G-protein interaction. Beta -arrestins are important not only in attenuating GPCR signaling in the continued presence of agonist, but also for receptor resensitization and down-regulation (Kilpatrick et al, 2012). These authors quantified neuropeptide Y receptor association with β-arrestins and observed internalization of NPY1R to clathrin-coated pits after recruitment by β-arrestins when subjected to the agonist effect of NPY.…”
Section: Discussionmentioning
confidence: 99%